ANALISIS HUBUNGAN KAUSALITAS PENGGUNAAN ENERGI, PERTUMBUHAN EKONOMI DAN EMISI LINGKUNGAN DI INDONESIA - Serdo Nurdi Putra; Alpon Satrianto (Universitas Negeri Padang, 2019)
This study aims to identify and analyze the relationship between energy use, economic growth and environmental emissions in Indonesia. The type of this research is associative descriptive research, where the data used is secondary data 1982-2016 which uses the Vector Error Correction Model (VECM) data to see the long and short term at the same time. The findings of this study indicate that there is no causality or unidirectional relationship between energy use and economic growth. There is no causal relationship or unidirectional relationship between economic growth and environmental emissions. There is a causal relationship between environmental emissions and energy use.